An investigation on the precipitates in T5 treated high vacuum die-casting AE44–2 magnesium alloy. (1st February 2022) - Li, Yongfeng; Wang, Jinhui; Ma, Hongbin; Zhen, Zisheng; Liu, Yanzhuo; Zhang, Honggang; Jin, Peipeng
Abstract: The AE44-2 magnesium alloy was fabricated via die-casting under high vacuum (denoted as HVDC-AE44-2 alloy). The microstructures and mechanical properties of the aged HVDC-AE44-2 alloys were investigated. It was found that age strengthening can be achieved in the HVDC-AE44-2 alloys.The hardness, the yield strengths (YS) and the ultimate tensile strengths (UTS) of the HVDC-AE44-2 alloys after aging at 200 °C for 12 h (T5) increased by 8.8 HV, 30.5 MPa and 22.6 MPa, respectively, while the the elongations remained almost at the same level (The elongation was 19.6% in the die casting. The elongation was 19.1% in aged at 200 ℃ for 12h). It was also found that the improved age hardening ability was closely related to the Al4 Mn and Al11 Mn4 precipitation during aging. Both the α -Mg and the Al11 RE3 have crystallographic orientation relationships with the Al4 Mn. The slipping of dislocations was impeded by the precipitates during tensile deformation at room temperature, and the 〈a〉 dislocations were accumulated around the precipitates, which is the reason for the increase of the HVDC-AE44-2 alloy strength.